Synthesis of Trisubstituted 1,2,4-Triazines in Presence of NaHSO4/SiO2 - Azizian, J.; Krimi, A.R. (Asian Journal of Chemistry, 2010)
An efficient method for the synthesis of trisubstituted 1,2,4-triazines, phenanthro-1,2,4-triazines and acenaphtho-1,2,4-triazines derivatives by three-component condensation of benzil or phenanthrene-9,10-dione or acenaphthylene-1,2-dione, with acid hydrazides and ammonium acetate using sodium bisulfate adsorbed on silica gel (NaHSO4/SiO2) as catalyst is reported.